Plant architecture evolution for higher yields in cluster bean (Cyamopsis tetragonoloba) under arid conditions - DADHEECH, RAMA; SHARMA, R; MAHLA, H R; BHATT, R K (The Indian Journal of Agricultural Sciences, 2020)
Cluster bean [Cyamopsis tetragonoloba (L.) Taub] is an annual legume well adapted to limiting soil moisture and wide range of temperature fluctuations. In order to realize the potential of the crop, systematic cluster bean improvement efforts in India were initiated since 1961. Early released varieties were identified through multilocation germplasm testing. Selections, hybridization and mutagenesis have been contributing to recent varieties with more shares emanating from hybridization. Some of the earlier released varieties are still popular with the farmers. The traits responsible for high yield in guar varieties have not been analyzed and probably resulting in release of similar types with no or marginal gains. Hence, present investigation was undertaken to evaluate popular varieties with respect to seed yield and other associated morpho-physiological traits. Thirty varieties procured from the Agriculture Research Station, Durgapura (SKRAU, Bikaner), CCHAU, Hisar and CAZRI, Jodhpur were evaluated during kharif 2013, 2014 and 2015 at the Central Research Farm, Central Arid Zone Research Institute, Jodhpur, India. The analysis of variance indicated non-significant variation for important yield and yield attributing traits like pods/plant, pod length, seed weight and nodes per plant. The various traits like branches per plant, number of clusters and pods per cluster complemented so as to have comparable number of pods per plant and yield. Most of the contribution to variance comes from environments indicating adaptive plasticity in cluster bean irrespective of varieties. The varieties released meticulously incorporated early partitioning and increased proportion of reproductive phase for high yield.